Origin of widespread Cretaceous alkaline magmatism in the Central Atlantic: A single melting anomaly? - Merle, Renaud; Jourdan, Fred; Chiaradia, M.; Olierook, Hugo; Manatschal, G. (ELSEVIER, 2019)
© 2019 Elsevier B.V. The age and origin of the Late Cretaceous magmatism on the North American and Iberian-African margins and the adjacent northern Central and Southern North Atlantic ocean are not well constrained due to the lack of appropriate data. To solve this issue, we used the 40Ar/39Ar geochronology and Sr-Nd-Pb isotopes geochemistry of basalts from the New England Seamounts (NES) and the J-Anomaly Ridge (JAR) as these localities on the North American margin are still poorly investigated. We obtained a reliable age of 82.39 ± 0.12 Ma (2σ) for the Nashville Seamount (NES) and an alteration age of ca. 76 Ma for the JAR. Our new dates from the New England Seamounts, combined with those available from the Tore–Madeira Rise and SW Portugal, on the Iberia–African margins, confirm an overlapping period of activity around 105-80 Ma on both the North American and Iberian-African margins and the adjacent oceanic basins. Plate kinematic reconstructions indicate that these magmatic occurrences were located within a ~1000 km radius within the yet narrow Atlantic Ocean. The J-Anomaly Ridge samples were most likely formed at the mid-Atlantic ridge around ~120 Ma. The Sr-Nd-Pb initial isotopic ratios from the New England seamounts show similarities with the chemical signature of the Tore–Madeira Rise and, to a lesser extent, SW Portugal. Moreover, New England Seamounts display a trend toward EMI isotopic end-member, similar to those documented in at the Late Cretaceous Godzilla seamount on the Tore–Madeira Rise and sills from ODP Site 1276. The shared chemical signature is distributed across a torus-shaped area of ~2000 × 2000 km at a near-fixed location on Earth and is not temporally-controlled, suggesting a large-scale chemical anomaly in the shallow mantle. Therefore, geochronological, geochemical and plate reconstructions imply a large-scale, anomalously fertile mantle source that generated widespread magmatism during the Late Cretaceous in the northern Central Atlantic.